1990
DOI: 10.1007/bf02764282
|View full text |Cite
|
Sign up to set email alerts
|

Posterior vitreous detachment following panretinal laser photocoagulation

Abstract: A total of 30 eyes of 19 patients with type I diabetes, varying severity of retinopathy, and no posterior vitreous detachment (PVD) were studied clinically, and vitreous examination was performed by preset lens biomicroscopy. Follow-up was 4.0-7.5 years. A total of 15 eyes underwent panretinal laser photocoagulation (PRP) and 15 eyes were left untreated. The incidence of PVD was 8 of 15 353%) after PRP and 1 of 15 (7%) in untreated eyes (P less than 0.02). Minimal vitreous hemorrhage occurred in 4 of 7 treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…Sebag and Nguyen-Cuu [30] reported that the risk of PDR is lower in eyes with PVD than in eyes with an attached vitreous, a well-established finding [31, 32]. It was hypothesized previously that PRP might provide therapeutic benefit by inducing a PVD, and studies have shown that the incidence of PVD was greater in patients treated with PRP than in those who did not, supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 51%
“…Sebag and Nguyen-Cuu [30] reported that the risk of PDR is lower in eyes with PVD than in eyes with an attached vitreous, a well-established finding [31, 32]. It was hypothesized previously that PRP might provide therapeutic benefit by inducing a PVD, and studies have shown that the incidence of PVD was greater in patients treated with PRP than in those who did not, supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 51%
“…Panretinal laser argon photocoagulation therapy has been shown to induce a total PVD over time 19. There is conflicting evidence on whether anti-VEGF injections induces changes in VRI status; a prospective observational study by Geck et al 20 including 61 eyes with a variety of retinal diseases showed development of a PVD in 15 out of 61 eyes (24.5%) while a cohort study by Veloso et al 21 investigating the development of a PVD in 396 eyes with age-related macular degeneration treated with anti-VEGF showed development of a PVD rarely (5.6% of eyes after an average of 8.3 injections).…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical findings indicated that PDVR is rare if the vitreous cortex has detached completely in myopics with PVD and after vitrectomy, since the scaffold for proliferating cells is destroyed [97]. In high myopia lesser diabetic involvements of the fundus oculi have been observed [57], which may serve as a proof for the involvement of the vitreous in the development of diabetic retinal changes and therefore justifies the term PDVR.…”
Section: Hypothetical Pathogenesis Of Pdvrmentioning
confidence: 99%